1978
DOI: 10.1103/physrevb.17.1455
|View full text |Cite
|
Sign up to set email alerts
|

Helium II thermal counterflow at large heat currents: Profound effects of geometry

Abstract: Data for the temperature difference produced by the thermal counterflo~of HeII in long glass tubes of rectangular cross section are given and compared to earlier data from circular tubes. Both geometries display a region of mutual friction described by the Vinen theory. In the circular tubes this region terminates at a critical heat current above which an additional source of dissipation is present. This critical heat current and dissipation are not observed in any of the three rectangular tubes studied. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…If the aspect ratio of the channel is high, the counterflow exhibits Fig. 2 Typical temperature and pressure difference ∆T and ∆p as a function of heat current Q for a circular flow tube at 1.7 K with thermal counterflow [26]. The broken line is an extrapolation of the linear region, consistent with Eq.…”
Section: Two-fluid Model and Thermal Counterflowsupporting
confidence: 62%
“…If the aspect ratio of the channel is high, the counterflow exhibits Fig. 2 Typical temperature and pressure difference ∆T and ∆p as a function of heat current Q for a circular flow tube at 1.7 K with thermal counterflow [26]. The broken line is an extrapolation of the linear region, consistent with Eq.…”
Section: Two-fluid Model and Thermal Counterflowsupporting
confidence: 62%
“…In Fig. 2, the critical Reynolds Re s = V c d/κ with κ being the quantum of circulation of 4 He is displayed for the datasets reported in ten papers published over a period of 25 years between 1960 and 1985 [25][26][27][28][29][30][31][32][33][34]. The datasets have been partitioned into three temperature ranges to better evidence a possible temperature dependence.…”
Section: A Critical Velocities In Superfluid Counterflowsmentioning
confidence: 99%
“…Different experiments conducted with a broad range of channel dimensions and over a broad temperature range have shown that in helium II three distinct turbulent states exist [36,37]. Two of the turbulent states called TI and TII occur in round and small aspect ratio channels whereas a third turbulent regime named TIII occurs in wide aspect ratio channels.…”
Section: Quantum Turbulence In Helium IImentioning
confidence: 99%